Ukrainian black soils in war: assessing the impact of hostilities on violations of the guidelines for sustainable soil management - Anatolii Kucher (Agricultural and Resource Economics)
Purpose. The purpose of the article is to highlight the results of the assessment of the degree and scale of violation of the Food and Agriculture Organization of the United Nations (FAO) guidelines for sustainable soil management due to hostilities, as well as the damage and losses caused to black soils (chernozems) at the level of the territorial community due to armed aggression.